2016
DOI: 10.1186/s12978-016-0238-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and awareness of genital involvement and reproductive health consequences of urogenital schistosomiasis in endemic communities in Ghana: a cross-sectional study

Abstract: BackgroundThe World Health Organization, in the year 2009, renamed Schistosomiasis haematobium disease, urinary schistosomiasis, as urogenital schistosomiasis. This study, sought to determine whether urogenital schistosomiasis endemic community members were aware of the broadened scope of the disease and associated certain reproductive health related signs and symptoms to S. haematobium infection.MethodThis is a cross-sectional study in which 2,585 respondents aged 15–49 years from 30 riparian communities alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 17 publications
(21 reference statements)
4
39
0
Order By: Relevance
“…Additionally, efforts have been made to develop FGS vaccines alongside HIV/AIDS vaccines, with several schistosomiasis vaccines now in clinical testing [36]. There are also efforts in place to improve local advocacy and health education around FGS [37].…”
mentioning
confidence: 99%
“…Additionally, efforts have been made to develop FGS vaccines alongside HIV/AIDS vaccines, with several schistosomiasis vaccines now in clinical testing [36]. There are also efforts in place to improve local advocacy and health education around FGS [37].…”
mentioning
confidence: 99%
“…The current findings highlight the significance of health education as a key component of the schistosomiasis control programs [ 31 , 51 , 55 ]. This is because such programs are said to improve awareness, knowledge and uptake of preventive chemotherapy [ 17 , 31 , 34 , 40 , 42 , 45 , 47 , 48 ], thus increasing the success of MDA programmes.…”
Section: Discussionmentioning
confidence: 93%
“… Practice: (i) 38.5% of males and 39.5% of females showed symptoms during the study period reported to have done nothing about their health condition, (ii) 23.3% of males and 29.7% of females were taking self-medication and (iii) only 23.3% of males and 29.7% of females visited a health facility. Yirenya-Tawiah et al [ 51 ] / 2016 To determine urogenital schistosomiasis awareness in terms of its scope and signs and symptoms Mixed method study using a structured questionnaire; 24 focus group discussions (FGDs) were also conducted 2585 respondents aged 15–49 years from 30 riparian communities/ Endemic communities in Ghana Socio-demographic factors: Males were more knowledgeable than females, 14.5% and 7.2% ( p = 0.001), respectively. Knowledge: 99.4% of male respondents and 88.7% of female respondents were aware of schistosomiasis as a waterborne disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our cases presented symptoms of MGS described in the literature, which can be mistaken for STI as in the example described in "Case 2," and, thus, incorrectly received routine syndromic STI management, 16 highlighting the mistaken diagnosis and mismanagement of MGS treatable with PZQ. 17,18 The changing clinical presentations and parasitological results of our cases highlight the challenges associated with MGS diagnosis and management, requiring the development of better, low-cost, accessible, sensitive, and specific diagnostic tests. Although real-time PCR demonstrates greater ability to incriminate most cases, it remains relatively expensive and not always available in endemic areas.…”
Section: Discussionmentioning
confidence: 98%